1995
DOI: 10.1084/jem.181.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Lyme disease caused by diverse Borrelia burgdorferi.

Abstract: SummaryDiversity and mutations in the genes for outer surface proteins (Osps) A and B ofBorrelia burgdorferi sensu lato (13, burgdorferi), the spirochetal agent of Lyme disease, suggests that a monovalent OspA or OspB vaccine may not provide protection against antigenically variable naturally occurring B, burgdorferi. We now show that OspA or OspB immunizations protect mice from tick-borne infection with heterogeneous/g burgdorferi from different geographic regions. This result is in distinct contrast to in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Most vaccine trials have used ticks infected in the laboratory with only B. burgdorferi sensu stricto (Gern et al 1994. One vaccine trial used a combination of ticks collected in the field in the northeast United States, California, Sweden, and Germany, as well as ticks exposed to characterized strains (Fikrig et al 1995). Fikrig et al (1995) showed that a single antigen produced from the OspA gene derived from B. burgdoiferi sensu stricto could afford protection against both B. burgdorferi sensu stricto and B. afzelii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most vaccine trials have used ticks infected in the laboratory with only B. burgdorferi sensu stricto (Gern et al 1994. One vaccine trial used a combination of ticks collected in the field in the northeast United States, California, Sweden, and Germany, as well as ticks exposed to characterized strains (Fikrig et al 1995). Fikrig et al (1995) showed that a single antigen produced from the OspA gene derived from B. burgdoiferi sensu stricto could afford protection against both B. burgdorferi sensu stricto and B. afzelii.…”
Section: Discussionmentioning
confidence: 99%
“…One vaccine trial used a combination of ticks collected in the field in the northeast United States, California, Sweden, and Germany, as well as ticks exposed to characterized strains (Fikrig et al 1995). Fikrig et al (1995) showed that a single antigen produced from the OspA gene derived from B. burgdoiferi sensu stricto could afford protection against both B. burgdorferi sensu stricto and B. afzelii. These researchers failed, however, to infect rodents with B. gflrinu-infected ticks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick transmission studies have also indicated a annular rash with central clearing that occurs at the site of the significant degree of vaccine-induced cross-protection between tick bite in Ç60% -80% of cases. Late-stage disease, which can spirochetes from different regions of the U.S. [9]. Following the initial phase I studies, a double-blind, placebocontrolled dose-range study was conducted in 350 healthy adult residents of three New England islands on which LD is highly vations: all doses were well tolerated, although mild local reac-10 states were selected for the pivotal trial.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…In istered 1 year later. Prolonged surveillance was employed because of the long latency period for the appearance of some 1993, a total of 8,285 cases of LD were reported to the CDC by 44 states, 15% less than the number of LD cases (9,677) of the symptoms (e.g., rheumatological and neurological manifestations) and because it will assist in addressing the issue of reported in the continental United States during 1992 [14].…”
Section: Vaccine Developmentmentioning
confidence: 99%